Is ischemia modified albumin a disease activity marker for inflammatory bowel diseases?. Issue 6 (June 2016) - Kaplan, Mustafa; Yuksel, Mahmut; Ates, Ihsan; Kilic, Zeki Mesut Yalın; Kilic, Hasan; Kuzu, Ufuk Barıs; Kayacetin, Ertugrul
Abstract: Background and Aim: We aimed to identify ischemia‐modified albumin (IMA) levels in inflammatory bowel disease (IBD) and IBD subgroups, and to examine its relation with disease activity index. Methods: Sixty‐eight patients with IBD (35 ulcerative colitis [UC] and 33 crohn disease [CD]) and 65 healthy volunteers were included in the study. Rachmilewitz scoring system (endoscopic activity index [EAI]) was used to determine UC activity, and as for CD activity, CD activity index (CDAI) scoring was used. IMA measurement was performed with ELISA kit. Results: Ischemia‐modified albumin levels in IBD, UC, and CD groups were comparably higher than the control group (37.7 ng/mL vs 42.4 ng/mL vs 36.4 ng/mL vs 21.8 ng/mL, respectively; P  < 0.05). In IBD group, a positive correlation was identified between IMA level and CRP ( r  = 0.325, P  = 0.011), EAI( r  = 0.302, P  = 0.020), and CDAI ( r  = 0.311, P  = 0.013). In stepwise regression model; it was identified that IMA(OR = 1.496; P  = 0.016) and CRP(OR = 3.457; P  = 0.015) are predictors of IBD in comparison with the control group. In linear regression model, it was identified that risk factors such as log(IMA) and log(CRP) were independent predictors of log(CDAI) and log(EAI) levels. Conclusion: This is the first study showing that IMA levels in IBD were determined higher in comparison with the control group. Moreover, IMA being a predictor for IBD and being positively correlated with disease activity indexes were determined for the first time in the study. In accordance with these results, it is possible to say that IMA in IBD might be related with the pathogenesis of disease and correlated with the severity of the disease.